Eficacia de las medidas de protección otorgadas a las víctimas de violencia familiar en los juzgados de familia de Maynas 2019 - Fernandez Tapia, Jemisuy Liliana (2023)
The present investigation deals with a very relevant topic for society, as it is, the granting of measures applied to protect the victim against events of violence. For this reason, the present study called "Efficacy of the protection measures granted to victims of family violence in the Family Courts of Maynas 2019", has as a problem: What is the level of effectiveness of the protection measures granted to victims of family violence in the Family Courts of Maynas 2019?, and as a general objective: Determine the level of effectiveness of the protection measures granted in favor of victims of family violence in the Family Courts of Maynas 2019. As a methodical part, the study is based from a quantitative point of view, of a basic type, of a descriptive level and of a non-experimental design, with legal research of a sociological type. In the same way, the population is made up of files from the Maynas Family Courts in which the adoption of measures aimed at supporting those affected by violence in 2019 has been requested and the sample is 150 files from the Court in question. Regarding the results of the study, 3.3% of protection measures aimed at protecting the victims were effective, while 96.7% of protection measures were ineffective. Ultimately, it is concluded that the measures aimed at safeguarding people affected by family violence are ineffective as they do not meet criteria such as: granted within the legally established term, the Peruvian National Police does not comply with its task of timely reporting the compliance with the protection measures, support to other institutions is not required for the execution of the protection measures, and the victims do not notify the competent body of noncompliance with the measures, which is extremely important for their effectiveness.